PRESENCE OF ARTHROPOD PESTS ON EIGHT SPECIES OF BANKER PLANTS IN A GREENHOUSE - Parolin, Pia (2013)
Despite precautions, the spontaneous invasion of undesired arthropod pests in greenhouses seems to be unavoidable. Secondary plants can be employed in biological control to enhance the proliferation of desired natural enemies of arthropod pests. However, these additional plants may also attract pests which in turn attack the crop plants. The present study is part of a long-term experiment to test eight species of banker plants (BPs) and their efficiency for biological protection against the spider mite Tetranychus urticae, employing the predatory mite Amblyseius californicus as natural enemy. Our goal was to find the best suited local plant species to be used as BPs, which enhances the reproduction and continuous release of the predators in a greenhouse. In the present paper, we document the spontaneous invasion of arthropods on eight species of BPs in a time span of three months, in a greenhouse in Southern France. The first arthropods appeared spontaneously on some of the plants after 4-8 weeks. After three months, there were 6 additional species of arthropods (whiteflies Trialeurodes vaporariorum, rose aphids Rhodobium porosum, gall midges Feltiella acarisuga, flower thrips Frankliniella occidentalis, parasitic wasps Encarsia sp. and predatory mites Phytoseiulus persimilis). Different species of plants attracted different species of arthropods. None of the pest arthropods reproduced on the available BPs in the experimental phase and thus did not represent a problem for the ornamental crop (rose plants). This shows that the mere presence of arthropods in a greenhouse might not affect the crop, as long as there is certain diversity of plant species. Although BPs may act as involuntary multipliers for pests, our study shows that, under the given conditions, this was not the case for the chosen BPs.